Engineering properties of acrylic emulsion polymer modified bamboo reinforced cement bonded composites. Issue 3 (3rd July 2017) - Akinyemi, Banjo A.; Omoniyi, Temidayo E.
Abstract: In this study, bamboo fibres from Bambusa Vulgaris species were used as reinforcement materials for acrylic emulsion polymer modified concrete to determine their engineering properties and elemental compositions. Moisture absorption, density and percentage voids were investigated as well as the compressive strength, flexural strength and split tensile strength at 28, 45 and 60 days of air curing. Acrylic polymers reduced moisture intake, increased the densities and led to another increase in percentage of voids but composite samples with bamboo fibre inclusions at 1.5% and 10% polymers with 1.5% fibre an 15% polymers showed better physical properties than those with polymers only. Compressive and split tensile strength tests had similar results of optimum strength at 45 days while flexural strength test had optimum value at 60 days of air curing. This showed that the properties of unreinforced concrete could be improved through addition of fibres and polymers for use in structural applications.